Values, Motives, and Organic Food Consumption in China: A Moderating Role of Perceived Uncertainty - Wei, Sheng; Liu, Furong; She, Shengxiang; Wu, Rong (Frontiers in Psychology, 2022)
The present research attempts to understand the importance of altruistic and egoistic values in determining consumers’ motives and intention to purchase organic foods. Using the face-to-face survey approach, a total of 1,067 responses were collected from consumers in China. Data analysis was performed using a two-step structural equation modeling (SEM) approach, i.e., measurement and structural models. The findings indicated that both values influence the intention to purchase organic foods through the mediation of motives. Specifically, the altruistic value influences the environmental concern (EC), and the egoistic value influences the health concern (HC). Moreover, the perceived uncertainty negatively moderates a relationship between consumer HC and organic purchase intention while positively moderating a relationship between consumer EC and organic purchase intention. Several implications and suggestions are also discussed.